(untitled) (Marketing Journal, 2025)
This article examines the current state and prospects of applying artificial intelligence (AI) technologies in digital marketing processes of higher education institutions in Uzbekistan. In October 2024, Uzbekistan approved the Strategy for the Development of AI Technologies until 2030, and announced a project to train 5 million AI leaders by 2030. The number of internet users in the country has reached 29.5 million, and higher education coverage has increased to 43%. The study analyzes the opportunities an d challenges of implementing AI technologies in Uzbekistanʼs higher education institutions and develops practical recommendations.